Peroxisomal disorders - Schrader, Michael (Henry Stewart Talks, 2026)
Major metabolic pathways in peroxisome, Classification of peroxisomal disorders, The Zellweger spectrum of peroxisome biogenesis disorders (PBDs), PBDs and mutations in PEX gene, Development of therapies for treatment of peroxisomal disorders